Tax progression under collective wage bargaining and individual effort determination - Erkki Koskela; Ronnie Schöb (Center for Economic Studies and ifo Institute (CESifo), 2007)
We study the impact of tax policy on wage negotiations, workers' effort, employment, output and welfare when workers' effort is only imperfectly observable. We show that the different wage-setting motives - rent sharing and effort incentives - reinforce the effects of partial tax policy measures but not necessarily those of more fundamental tax reforms. Although a higher degree of tax progression always leads to wage moderation, the well-established result from the wage bargaining literature that a revenue-neutral increase in the degree of tax progression is good for employment does not carry over to the case with wage negotiations and imperfectly observable effort. While it remains true that introducing tax progression increases employment and output, we cannot rule out negative effects from an increase in tax progression when tax progression is already very high. Welfare effects are ambiguous a priori but we derive sufficient conditions for welfare improving revenue-neutral increases in tax progression.
Keywords: J41; J51; H22; 330; Steuerprogression; Steuerwirkung; Lohnverhandlungstheorie; Leistungsmotivation; Beschäftigungseffekt; Makroökonomischer Einfluss; Theorie